What lies hidden behind structural errors and failures within the UK?. Issue 4 (10th June 2019) - Burrell, Paul A
Abstract : Government figures from a House of Commons research briefing confirms that the components of the gross domestic product by industry are accounted for by the service sector at 79%, production at 14%, construction at 6% and agriculture at 1%. In its 2018 construction statistics, the Office for National Statistics (ONS) records that the construction industry is worth c. £100 billion annually to the UK economy. However, the Get it Right Initiative suggested in 2017 that a minimum of 10% of this is lost in errors and litigation. According to the ONS figures there were 30 fatalities. To investigate these errors and failures, this paper considers key areas in the education of chartered engineers, quality management systems and knowledge sharing in order to gain experience. A series of open-ended, semi-structured interviews was undertaken with senior professionals, including the judiciary, professors of engineering, global consultants and professional indemnity insurers. Research findings revealed that technical knowledge is deliberately withheld due to non-disclosure clauses in mediated settlements and through the practices of global professional indemnity insurers. A study of pass rates for chartered membership of the Institution of Structural Engineers showed a decrease despite an increase in academic requirements. Companies that promote corporate social responsibility credentials often seek the best commercial deal regarding litigation settlement. This research concludes that there is a sound business case for sharing knowledge, which would reduce claims, increase profits and save lives. Primary legislation must be changed to compel a free exchange of technical knowledge regarding errors and structural failures. A 'no-blame' repository needs to be established that should help reduce the adversarial nature of the construction industry. Additionally, the suitability of the academic degree curriculum for structural engineers needs to be reassessed.